The Elderly Chronic Diseases in China - Xiao, Shuyue (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The world is gradually entering an aging society, and chronic diseases are also one of the public problems plaguing the world. This article mainly discusses the problems of chronic disease management of the elderly in China’s current society from the aspects of economy, psychology and wisdom health. How to effectively manage chronic diseases and multimorbidity of the elderly.